Whereas it has been found requisite that certain alterations should take place in the table of fees, heretofore established for the several courts of this island, and the following appearing to me to be just and reasonable--I do hereby approve thereof, and such fees are in the future . given under my hand and seal at Fort Townshend, St. John's, Newfoundland, this first day of October, one thousand eight hundred and ten . [electronic resource]. - Duckworth, John Thomas, Sir. ([S.l. : s.n., 1810)
Printed ephemera. At head of title: By Sir John Thomas Duckworth, K.B., admiral of the blue, governor and commander in chief, in and over the island of Newfoundland, and its dependencies. Electronic reproduction. Mode of access: Internet. 44